Comparison of marketing mix dimensions between local and international hotel customers in Malaysia - Sanib, Noor Izza Rozian; Abdul Aziz, Yuhanis; Samdin, Zaiton; Ab Rahim, Khalid (Faculty of Economics and Management, Universiti Putra Malaysia, 2013)
The main purpose of this paper is to compare the perception of local and international customer of marketing mix components in the hotel industry in Malaysia. The exploratory study involved 282 respondents, employed self-completed questionnaire survey to collect data from local and international hotel customers. T-test analysis and One-way ANOVA are used to identify the significant mean difference of marketing mix components between local and international hotel customer. The main finding indicated that the three components of marketing mix namely product and services, promotion and people have significant differences between the means for both local and international hotel customers. This study also revealed that the product/services and promotion also had significance mean difference between the means of male and female hotel customer. Implications and limitations of the study are also discussed.